Recent Progress and Emerging Application Areas for Lithium–Sulfur Battery Technology - Doerfler, Susanne; Walus, Sylwia; Locke, Jacob; Fotouhi, Abbas; Auger, Daniel J.; Shateri, Neda; Abendroth, Thomas; Haertel, Paul; Althues, Holger; Kaskel, Stefan (Energy Technology, 2021)
Electrification is progressing significantly within the present and future vehicle sectors such as large commercial vehicles (e.g., trucks and buses), high-altitude long endurance (HALE), high-altitude pseudosatellites (HAPS), and electric vertical take-off and landing (eVTOL). The battery systems’ performance requirements differ across these applications in terms of power, cycle life, system cost, etc. However, the need for high gravimetric energy density, 400 Wh kg−1 and beyond, is common across them all, as it enables vehicles to achieve extended range, a longer mission duration, lighter weight, or increased payload. The system-level requirements of these emerging applications are broken down into the component-level developments required to integrate Li–S technology as the power system of choice. To adapt batteries’ properties, such as energy and power density, to the respective application, the academic research community has a key role to play in component-level development. However, materials and component research must be conducted within the context of a viable Li–S cell system. Herein, the key performance benefits, limitations, modeling, and recent progress of the Li–S battery technology and its adaption toward real-world application are discussed.
CRIS-Team Scopus Importer:2022-04-14
Keywords: applications; battery management systems; lithium sulfur batteries; prototype cells